Characterization of CaV1.2 exon 33 heterozygous knockout mice and negative correlation between Rbfox1 and CaV1.2 exon 33 expressions in human heart failure. Issue 1 (1st January 2018) - Wang, Juejin; Li, Guang; Yu, Dejie; Wong, Yuk Peng; Yong, Tan Fong; Liang, Mui Cheng; Liao, Ping; Foo, Roger; Hoppe, Uta C.; Soong, Tuck Wah
ABSTRACT: Recently, we reported that homozygous deletion of alternative exon 33 of CaV 1.2 calcium channel in the mouse resulted in ventricular arrhythmias arising from increased CaV 1.2Δ33 ICaL current density in the cardiomyocytes. We wondered whether heterozygous deletion of exon 33 might produce cardiac phenotype in a dose-dependent manner, and whether the expression levels of RNA splicing factors known to regulate alternative splicing of exon 33 might change in human heart failure. Unexpectedly, we found that exon 33 +/− cardiomyocytes showed similar CaV 1.2 channel properties as wild-type cardiomyocyte, even though CaV 1.2Δ33 channels exhibit a gain-in-function. In human hearts, we found that the mRNA level of splicing factor Rbfox1, but not Rbfox2, was downregulated in dilated cardiomyopathy, and CACNA1C mRNA level was dramatically decreased in the both of dilated and ischemic cardiomyopathy. These data imply Rbfox1 may be involved in the development of cardiomyopathies via regulating the alternative splicing of CaV 1.2 exon 33. (149 words)